2020
DOI: 10.26737/jerr.v3i1.2015
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Koneksi Matematis Siswa Pada Materi Trigonometri

Abstract: <em>Penelitian ini bertujuan untuk mendeskripsikan tingkat kemampuan koneksi matematis siswa, kesalahan siswa dalam menyelesaikan soal trigonometri berdasarkan indikator kemampuan koneksi matematis siswa, dan faktor yang mempengaruhi siswa melakukan kesalahan dalam menyelesaikan soal trigonometri berdasarkan indikator kemampuan koneksi matematis siswa pada kelas XI di SMA Negeri 10 Singkawang. Penelitian ini menggunakan description research. Subjek penelitian ini adalah 30 siswa kelas XI IPA di SMA Neger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Students have not been able to analyze the relationship between information and concepts and existing questions and have not been able to identify relationships between questions and concepts (47) . Factors that influence students' ability to relate data are low conceptual understanding, lack of language mastery of question requests, lack of accuracy and forgetting the formula to be used, low reasoning ability (48) . The ability of the conclusion indicator is measured with 2 questions.…”
Section: Methodsmentioning
confidence: 99%
“…Students have not been able to analyze the relationship between information and concepts and existing questions and have not been able to identify relationships between questions and concepts (47) . Factors that influence students' ability to relate data are low conceptual understanding, lack of language mastery of question requests, lack of accuracy and forgetting the formula to be used, low reasoning ability (48) . The ability of the conclusion indicator is measured with 2 questions.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, many studies have found that students are still relatively weak in their math connection ability. One of them is research by Kenedi et al (2019) Hanarafa (2021, Ningsih et al, (2020), andHati et al, (2022) which indicates that students have a relatively low level of mathematical connection ability. In addition to the selection of learning models that must be appropriate, the ability to tolerate adversity is an important aspect of a person's quality of life known as the Adversity Quotient (AQ).…”
Section: Introductionmentioning
confidence: 99%